Matrix cracking onset stress and strain as a function of temperature, and characterisation of damage modes in SiCf/SiC ceramic matrix composites via acoustic emission. Issue 7 (July 2023) - Quiney, Z.; Jeffs, S.P.; Gale, L.; Pattison, S.; Bache, M.R.
Abstract: The complex damage mechanisms that accumulate within SiCf /SiC ceramic matrix composites (CMCs) subject to thermal and mechanical stress are being investigated in anticipation of the material's introduction into high performance gas turbine engines. Acoustic emission (AE) is recognised as a leading non-destructive evaluation (NDE) tool to this end, and was used in this study to determine the so-called matrix cracking onset stress under tensile load as a function of temperature up to a maximum of 1100 °C. Onset stress was interpreted using three traditional measurements based on AE energy characteristics during monotonic tests to failure. Pattern recognition (PR) analysis was performed on the AE data, revealing a specific cluster of signals that correlated closely with the initial matrix cracking region of the stress-strain curve. Taken in isolation, the onset stress of this activity was significantly lower than the conventional value. PR results were investigated further, and isolated clusters were linked to damage modes anticipated at other specific regions of the stress history. A secondary series of experiments was performed on specimens representing the individual constituents of the CMC (single-phase SiC flexural bars, Hi-Nicalon™ fibre bundles and SiCf /SiC mini-composites) in attempts to further validate the corresponding AE signal characteristics. Matrix cracking and interphase debonding/sliding damage modes could be identified consistently, while fibre breaks remained difficult to isolate under the current experimental conditions.